Wear-resistant and corrosion-resistant material for overflowing part of slurry pump and preparation method of wear-resistant and corrosion-resistant material

By adjusting the composition ratio of the slurry pump material and adding titanium iron breeding agents and tadpole breeding agents, the problem of abrasion resistance and corrosion resistance in the strong acid environment in a strong acid environment is solved, and a high resistance The abrasive and corrosive alloy materials meet the application needs of the coloring mine extraction process.

CN119351899AInactive Publication Date: 2025-01-24HEBEI TIIEC MASCH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411490626.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing slurry pump materials are difficult to have both wear resistance and corrosion resistance in strong acid environments. High chromium plates have good wear resistance but poor corrosion resistance, while titanium alloys are corrosion-resistant but not wear-resistant.

Method used

By adjusting the material component ratio and adding titanium-iron inoculants and vanadium-iron inoculants, an alloy material with both wear resistance and corrosion resistance is prepared.

Benefits of technology

It achieves high wear resistance and corrosion resistance of the material in a strong acid environment, meeting the application needs of slurry pumps in non-ferrous ore extraction processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351899A_ABST
    Figure CN119351899A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of metal materials, and particularly relates to a wear-resistant and corrosion-resistant material for an overflowing part of a slurry pump and a preparation method thereof.The wear-resistant and corrosion-resistant material for the overflowing part of the slurry pump comprises, by mass, 1.4-2 parts of C, 0.8-1.5 parts of Si, 0.8-1.2 parts of Mn, 33-38 parts of Cr, 2-2.5 parts of Mo, 5.5-6.5 parts of Ni, 1-2 parts of Cu, 0.4-0.8 part of a ferrotitanium inoculant, 0.1-0.5 part of a ferrovanadium inoculant and 46-53.7 parts of Fe. The ferrotitanium inoculant and the ferrovanadium inoculant are added while the composition proportion of the material is adjusted, so that the prepared wear-resistant and corrosion-resistant material has both wear resistance and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal materials, and in particular relates to a wear-resistant and corrosion-resistant material for a flow-through part of a slurry pump and a preparation method thereof. Background Art

[0002] In the process of extracting metals from non-ferrous ores, strong acids are often used. Therefore, the ore slurry contains a higher concentration of acidic media in the later stage. Therefore, the material requirements for the slurry pump used to transport the slurry are also high, and it needs to have good corrosion resistance and wear resistance.

[0003] Most commercially available slurry pumps are made of high chromium plates or titanium alloys. High chromium plates have good wear resistance and a Rockwell hardness of over 50, but poor corrosion resistance in strong acids; and although titanium alloys can meet the requirements of corrosion resistance, they are not wear-resistant. Therefore, a material with both corrosion resistance and wear resistance is needed for the production of slurry pumps. Summary of the invention

[0004] In order to solve the problems existing in the above-mentioned prior art, the present invention provides a wear-resistant and corrosion-resistant material for a slurry pump flow part and a preparation method thereof. By adjusting the material composition ratio and adding a titanium-ferro inoculant and a vanadium-ferro inoculant, the prepared wear-resistant and corrosion-resistant material has both wear resistance and corrosion resistance.

[0005] The specific technical solution adopted by the present invention is: A wear-resistant and corrosion-resistant material for flow parts of a slurry pump, comprising, by mass, 1.4-2 parts of C, 0.8-1.5 parts of Si, 0.8-1.2 parts of Mn, 33-38 parts of Cr, 2-2.5 parts of Mo, 5.5-6.5 parts of Ni, 1-2 parts of Cu, 0.4-0.8 parts of titanium-iron inoculant, 0.1-0.5 parts of vanadium-iron inoculant, and 46-53.7 parts of Fe.

[0006] Furthermore, the wear-resistant and corrosion-resistant material includes, by mass, 1.5-1.8 parts of C, 1-1.3 parts of Si, 0.9-1.1 parts of Mn, 34.5-36.5 parts of Cr, 2.1-2.3 parts of Mo, 5.8-6.2 parts of Ni, 1.4-1.7 parts of Cu, 0.5-0.7 parts of titanium-iron inoculant, 0.2-0.4 parts of vanadium-iron inoculant, and 47-51.5 parts of Fe.

[0007] Furthermore, the wear-resistant and corrosion-resistant material includes, by mass, 1.6 parts of C, 1.2 parts of Si, 1 part of Mn, 35 parts of Cr, 2.2 parts of Mo, 6 parts of Ni, 1.5 parts of Cu, 0.6 parts of ferrotitanium inoculant, 0.3 parts of ferrovanadium inoculant, and 50.5 parts of Fe.

[0008] Furthermore, the impurity P content in the wear-resistant and corrosion-resistant material is less than or equal to 0.1wt%, and the S content is less than or equal to 0.06wt%.

[0009] Furthermore, the vanadium content in the ferrovanadium inoculant is 55-65%, and the titanium content in the ferrotitanium inoculant is 35-45%.

[0010] Furthermore, the block sizes of the ferrotitanium inoculant and the ferrovanadium inoculant are both ≤10 mm.

[0011] A method for preparing a wear-resistant and corrosion-resistant material for a slurry pump flow part comprises the following steps: S1. Add scrap steel and ferromolybdenum into the furnace for heating and melting. After all of them are melted, add ferrochrome, electrolytic copper plate and nickel plate into the furnace in turn and heat to melt. Add ferromanganese 25-35 min before melting, mix well to form alloy liquid. S2. After melting, control the temperature to 1500-1550℃, then add ferrovanadium inoculant and ferrotitanium inoculant into the furnace, and melt and take out of the furnace after 10-20 minutes; S3, 0.1-0.2% of yttrium-based rare earth by weight of molten iron is placed in the ladle, and then the molten iron is poured into the ladle, allowed to stand, and slag is removed. When the temperature in the ladle reaches 1450°C-1460°C, casting is performed to obtain a casting; S4. After cleaning the casting, heat treatment is performed in a heat treatment furnace to obtain a wear-resistant and corrosion-resistant material.

[0012] Furthermore, the specific process of the heat treatment includes the following steps: S411. After cleaning the casting, place it in a heat treatment furnace. When the temperature in the furnace is less than 500°C, heat it up at a rate of 23-28°C per hour, then heat it up to 850°C at a rate of 48-52°C per hour. After keeping it at this temperature for 4-5 hours, take it out of the furnace and air cool it. S412, then put the air-cooled casting back into the heat treatment furnace, take room temperature as the initial temperature and heat it up to 250°C at a rate of 28-32°C per hour, then keep it warm for 4-5 hours, take it out of the furnace and air-cool it to obtain a wear-resistant and corrosion-resistant material.

[0013] The beneficial effects of the present invention are: 1. In the present invention, by adjusting the material composition ratio and adding a titanium-iron inoculant and a vanadium-iron inoculant, the wear-resistant and corrosion-resistant material has both wear resistance and corrosion resistance.

[0014] In the process of improving alloy materials, in order to improve the corrosion resistance of the materials, the proportion of Cr and Ni in the alloy materials is usually increased. However, too high Cr and Ni contents will make the alloy materials brittle and prone to pitting and intergranular corrosion, which will lead to a significant decrease in the wear resistance and corrosion resistance of the materials. Therefore, the Cr content of the alloy materials currently used for slurry pump production is generally 20-30wt%, and the Ni content is generally 1-2wt%.

[0015] However, the Cr content of the material in the present invention is as high as 33-38wt%, and the Ni content is as high as 5.5-6.5wt%. This is because ferrotitanium inoculant and ferrovanadium inoculant are added to the composition ratio of the alloy material in the present invention. The compounding of ferrotitanium inoculant and ferrovanadium inoculant can improve the crystallization state of the material, reduce lattice defects, and improve the stability of grain boundaries, thereby improving the problems of brittle material and uneven grain structure caused by high Cr and high Ni.

[0016] 2. Austenite is also generated in the alloy material of the present invention. Although austenite has good plasticity and toughness, and can improve the brittleness of the material caused by high Cr to improve the impact strength of the material, the crystal structure of austenite is relatively loose and the interatomic binding energy is low, resulting in the material's weak resistance to external chemical erosion, which in turn reduces the corrosion resistance of the material.

[0017] A sufficient amount of Ni can promote the solid solution strengthening of the austenite grain boundaries, thereby making the austenite evenly distributed and improving the crystal structure of the austenite, thereby improving the corrosion resistance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The metallographic diagram of the material prepared by the present invention. DETAILED DESCRIPTION

[0019] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments: The embodiments and comparative examples were smelted according to the composition ratio in Table 1, wherein the difference between comparative example 1 and embodiment 1 is that no ferrotitanium inoculant and ferrovanadium inoculant were added in comparative example 1; The difference between Comparative Example 2 and Example 2 is that in Comparative Example 2, a ferro-titanium inoculant is added, but no ferro-vanadium inoculant is added; The difference between Comparative Example 3 and Example 1 is that no ferro-titanium inoculant is added, and ferro-vanadium inoculant is added, and the ratio is: The difference between Comparative Example 4 and Example 1 is that the Ni content is increased. The specific composition ratio is shown in Table 1.

[0020] The preparation process in the embodiments and comparative examples is as follows: Example 1 S1. Add scrap steel and ferromolybdenum into the furnace for heating and melting. After all of them are melted, add ferrochrome, electrolytic copper plate and nickel plate into the furnace in turn and heat to melt. Add ferromanganese 30 minutes before melting, mix well to form alloy liquid. S2. After melting, control the temperature to 1520°C, then add ferrovanadium inoculant and ferrotitanium inoculant into the furnace, and melt and remove from the furnace after 15 minutes; S3, 0.2% of the weight of yttrium-based rare earth is placed in the ladle, and then the molten iron is poured into the ladle, allowed to stand, and slag is removed. When the temperature in the ladle reaches 1455°C, casting is performed to obtain a casting; S411, after cleaning the casting, place it in a heat treatment furnace, and when the temperature in the furnace is less than 500°C, heat it up at a rate of 25°C per hour, then heat it up to 850°C at a rate of 50°C per hour, keep it at that temperature for 4 hours, then take it out of the furnace for air cooling; S412, then put the casting after air cooling back into the heat treatment furnace, take room temperature as the initial temperature and heat it up to 250°C at a rate of 30°C per hour, then keep it at that temperature for 4 hours, take it out of the furnace and air cool it to obtain the wear-resistant and corrosion-resistant material.

[0021] Example 2 S1. Add scrap steel and ferromolybdenum into the furnace for heating and melting. After all of them are melted, add ferrochrome, electrolytic copper plate and nickel plate into the furnace in turn and heat to melt. Add ferromanganese 25 minutes before melting, mix well to form alloy liquid. S2. After melting, control the temperature to 1550°C, then add ferrovanadium inoculant and ferrotitanium inoculant into the furnace, and melt and remove from the furnace after 10 minutes; S3, 0.15% of the weight of yttrium-based rare earth is placed in the ladle, and then the molten iron is poured into the ladle, allowed to stand, and slag is removed. When the temperature in the ladle reaches 1450°C, casting is performed to obtain a casting; S411, after cleaning the casting, place it in a heat treatment furnace, and when the temperature in the furnace is less than 500°C, heat it at a rate of 28°C per hour, then heat it to 850°C at a rate of 52°C per hour, keep it at that temperature for 5 hours, then take it out of the furnace for air cooling; S412, then put the casting after air cooling back into the heat treatment furnace, take room temperature as the initial temperature and heat it to 250°C at a rate of 32°C per hour, then keep it at that temperature for 5 hours, take it out of the furnace and air cool it to obtain the wear-resistant and corrosion-resistant material.

[0022] Example 3 S1. Add scrap steel and ferromolybdenum into the furnace for heating and melting. After all of them are melted, add ferrochrome, electrolytic copper plate and nickel plate into the furnace in turn and heat to melt. Add ferromanganese 35 minutes before melting, mix well to form alloy liquid. S2. After melting, control the temperature to 1500°C, then add ferrovanadium inoculant and ferrotitanium inoculant into the furnace, and melt and remove from the furnace after 20 minutes; S3, 0.1% of the weight of yttrium-based rare earth is placed in the ladle, and then the molten iron is poured into the ladle, allowed to stand, and slag is removed. When the temperature in the ladle reaches 1460°C, casting is performed to obtain a casting; S411, after cleaning the casting, place it in a heat treatment furnace, and when the temperature in the furnace is less than 500°C, heat it at a rate of 23°C per hour, then heat it to 850°C at a rate of 52°C per hour, keep it at that temperature for 4 hours, then take it out of the furnace for air cooling; S412, then put the air-cooled casting back into the heat treatment furnace, take room temperature as the initial temperature and heat it up to 250°C at a rate of 32°C per hour, then keep it at that temperature for 4 hours, take it out of the furnace and air-cool it to obtain a wear-resistant and corrosion-resistant material.

[0023] Example 4 S1. Add scrap steel and ferromolybdenum into the furnace for heating and melting. After all of them are melted, add ferrochrome, electrolytic copper plate and nickel plate into the furnace in turn and heat to melt. Add ferromanganese 28 minutes before melting, mix well to form alloy liquid. S2. After melting, control the temperature to 1510°C, then add ferrovanadium inoculant and ferrotitanium inoculant into the furnace, and melt and remove from the furnace after 18 minutes; S3, 0.18% of the weight of yttrium-based rare earth is placed in the ladle, and then the molten iron is poured into the ladle, allowed to stand, and slag is removed. When the temperature in the ladle reaches 1458°C, casting is performed to obtain a casting; S411, after cleaning the casting, place it in a heat treatment furnace, and when the temperature in the furnace is less than 500°C, heat it up at a rate of 26°C per hour, then heat it up to 850°C at a rate of 50°C per hour, keep it at that temperature for 4.5 hours, then take it out of the furnace for air cooling; S412, then put the air-cooled casting back into the heat treatment furnace, take room temperature as the initial temperature and heat it up to 250°C at a rate of 30°C per hour, then keep it at that temperature for 4.5 hours, take it out of the furnace and air-cool it to obtain a wear-resistant and corrosion-resistant material.

[0024] The process parameters of the preparation steps of Example 5, Example 6 and Comparative Examples 1-4 are the same as those of Example 1.

[0025] Alloy materials were manufactured according to the proportions in Examples 1-6 and Comparative Examples 1-4, and then performance tests were performed respectively. The test results are shown in Table 2.

[0026] The performance requirements of materials for slurry pump flow parts are as follows: Hardness ≥ 40 HRC; Impact resistance index ≥8 KV2 / J; Mass wear ≤1.5mg; Corrosion rate (pH=2) ≤1.0mm / a; The hardness is tested by Rockwell hardness tester, and the average value is obtained by taking at least 5 points with a distance greater than 3mm from each other on the material; The impact value test is carried out according to GB / T 229-2007 "Charpy Pendulum Impact Test for Metallic Materials". The larger the impact value, the better the impact resistance of the material.

[0027] The quality wear test is carried out according to GB / T 12444-2006 "Metallic material wear test method test ring-test block sliding wear test". The smaller the wear value, the better the wear resistance of the material. The corrosion rate is the rate of immersion of the alloy material in 70℃, Cl - In H2SO4 solution with a content of 60000PPM and PH=2.

[0028] The wear-resistant and corrosion-resistant materials prepared in Examples 1-6 of the present invention have a hardness of ≥44 HRC, an impact value of ≥10.6KV2 / J, and a corrosion rate of ≤0.68 in a H2SO4 solution with a pH of 2, which meets the application requirements of non-ferrous mine extraction conditions and has both wear resistance and corrosion resistance.

Claims

1. A wear-resistant and corrosion-resistant material for a slurry pump flow part, characterized in that: Calculated by mass, it includes: 1.4-2 parts of C, 0.8-1.5 parts of Si, 0.8-1.2 parts of Mn, 33-38 parts of Cr, 2-2.5 parts of Mo, 5.5-6.5 parts of Ni, 1-2 parts of Cu, 0.4-0.8 parts of ferro-titanium inoculant, 0.1-0.5 parts of ferro-vanadium inoculant, and 46-53.7 parts of Fe.

2. The wear-resistant and corrosion-resistant material for flow parts of a slurry pump according to claim 1, characterized in that: The wear-resistant and corrosion-resistant material comprises, by mass, 1.5-1.8 parts of C, 1-1.3 parts of Si, 0.9-1.1 parts of Mn, 34.5-36.5 parts of Cr, 2.1-2.3 parts of Mo, 5.8-6.2 parts of Ni, 1.4-1.7 parts of Cu, 0.5-0.7 parts of ferro-titanium inoculant, 0.2-0.4 parts of ferro-vanadium inoculant, and 47-51.5 parts of Fe.

3. The wear-resistant and corrosion-resistant material for flow parts of a slurry pump according to claim 1, characterized in that: The wear-resistant and corrosion-resistant material includes, by mass, 1.6 parts of C, 1.2 parts of Si, 1 part of Mn, 35 parts of Cr, 2.2 parts of Mo, 6 parts of Ni, 1.5 parts of Cu, 0.6 parts of ferrotitanium inoculant, 0.3 parts of ferrovanadium inoculant, and 50.5 parts of Fe.

4. The wear-resistant and corrosion-resistant material for flow parts of a slurry pump according to claim 1, characterized in that: The impurity P content in the wear-resistant and corrosion-resistant material is less than or equal to 0.1wt%, and the impurity S content is less than or equal to 0.06wt%.

5. The wear-resistant and corrosion-resistant material for flow parts of a slurry pump according to claim 1, characterized in that: The vanadium content of the ferrovanadium inoculant is 55-65%, and the titanium content of the ferrotitanium inoculant is 35-45%.

6. The wear-resistant and corrosion-resistant material for flow parts of a slurry pump according to claim 1, characterized in that: The block sizes of the ferro-titanium inoculant and the ferro-vanadium inoculant are both ≤10 mm.

7. A method for preparing a wear-resistant and corrosion-resistant material for a slurry pump flow component according to claim 1, characterized in that: The following steps are involved: S1. Add scrap steel and ferromolybdenum into the furnace for heating and melting. After all of them are melted, add ferrochrome, electrolytic copper plate and nickel plate into the furnace in turn and heat to melt. Add ferromanganese 25-35 min before melting, mix well to form alloy liquid. S2. After melting, control the temperature to 1500-1550℃, then add ferrovanadium inoculant and ferrotitanium inoculant into the furnace, and melt and take out of the furnace after 10-20 minutes; S3, 0.1-0.2% of yttrium-based rare earth by weight of molten iron is placed in the ladle, and then the molten iron is poured into the ladle, allowed to stand, and slag is removed. When the temperature in the ladle reaches 1450°C-1460°C, casting is performed to obtain a casting; S4. After cleaning the casting, heat treatment is performed in a heat treatment furnace to obtain a wear-resistant and corrosion-resistant material.

8. The method for preparing the wear-resistant and corrosion-resistant material for the flow parts of a slurry pump according to claim 7, characterized in that: The specific process of the heat treatment comprises the following steps: S411. After cleaning the casting, place it in a heat treatment furnace. When the temperature in the furnace is less than 500°C, heat it up at a rate of 23-28°C per hour, then heat it up to 850°C at a rate of 48-52°C per hour. After keeping it at this temperature for 4-5 hours, take it out of the furnace and air cool it. S412, then put the air-cooled casting back into the heat treatment furnace, take room temperature as the initial temperature and heat it up to 250°C at a rate of 28-32°C per hour, then keep it warm for 4-5 hours, take it out of the furnace and air-cool it to obtain a wear-resistant and corrosion-resistant material.

Citation Information

Patent Citations

  • High-chromium cast iron and preparation method thereof

    CN114395721A

  • High-chromium acid-resistant cast iron material as well as preparation method and application thereof

    CN114769509A

  • High-chromium cast iron with high corrosion resistance and wear resistance as well as preparation method and application of high-chromium cast iron

    CN117051315A